Loss of p53 synthesis in zebrafish tumors with ribosomal protein gene mutations - MacInnes, Alyson W. (National Academy of Sciences, 2008)
Zebrafish carrying heterozygous mutations for 17 different ribosomal protein (rp) genes are prone to developing malignant peripheral nerve sheath tumors (MPNSTs), a tumor type that is seldom seen in laboratory strains of zebrafish. Interestingly, the same rare tumor type arises in zebrafish that are homozygous for a loss-of-function point mutation in the tumor suppressor gene p53. For these reasons, and because p53 is widely known to be mutated in the majority of human cancers, we investigated the status of p53 in the rp(+/−) MPNSTs. Using monoclonal antibodies that we raised to zebrafish p53, we found that cells derived from rp(+/−) MPNSTs are significantly impaired in their ability to produce p53 protein even in the presence of a proteasome inhibitor and γ-irradiation. Although the coding regions of the p53 gene remain wild type, the gene is transcribed, and overall protein production rates appear normal in rp(+/−) MPNST cells, p53 protein does not get synthesized. This defect is observed in all MPNSTs we examined that were derived from our 17 zebrafish lines with rp gene mutations. To date, studies of p53 in malignancies have focused predominantly on either p53 gene mutations or the aberrant posttranslational regulation of the p53 protein. Our results show that the appropriate amount of numerous ribosomal proteins is required for p53 protein production in vivo and that disruption of this regulation most likely contributes to tumorigenesis.